Solution and solid-state interactions in a supramolecular ruthenium photosensitizer-polyoxometalate aggregate - Heußner, Kirsten; Peuntinger, Katrin; Rockstroh, Nils; Nye, Leanne; Ivanovic-Burmazovic, Ivana; Rau, Sven; Streb, Carsten (Chemical Communications, 2011)
The intermolecular interactions between a ruthenium-based photosensitizer ([Ru(tbbpy)(biH)]) and a molecular metal oxide ([β-MoO]) are investigated in solution and in the solid state. The supramolecular interactions were studied using H-NMR, UV-Vis and emission spectroscopy, ESI mass spectrometry and single-crystal X-ray diffraction. The formation of supramolecular aggregates was observed both in the crystal lattice and in solution. In addition, it is shown that aggregation in solution can be controlled by the competitive formation of ion pairs. © 2011 The Royal Society of Chemistry.